Research of Crash Energy Management System for a Mass Transit Vehicle - Pei LIU; Caiying MI; Jingjing CHEN (机车电传动)
In order to improve the crashworthiness performance of a mass transit vehicle body, a crash energy management (CEM)system based on honeycomb aluminum core and tapered thin-walled square tube structure was established according to the requirements of American AAR S-034 standards. And the impact performance of CEM subsystem was analyzed by using the LS-DYNA platform. Then, the force-displacement curve and acceleration-time curve of the vehicle before and after the installation of the CEM system were compared under the scenario of impacting with a rigid obstacle. This research showed that, the "aluminum core-thin wall tube" combined energy-absorbing structure can make the crushing deformation process in an orderly manner and has a lower initial peak impact force; using the CEM system designed could significantly improve the crashworthiness performance of end structure of the vehicle.